Sequelae of preterm birth over the lifespan: an exploratory analysis of behavioral problems in childhood and increased risk of major depression and anxiety in adulthood from a cohort study - Fieß, Achim; Hartmann, Alica; Ernst, Mareike; Schuster, Alexander K.; Mildenberger, Eva; Brähler, Elmar; Urschitz, Michael S.; Pfeiffer, Norbert; Beutel, Manfred E.; Gißler, Sandra; Tesarz, Jonas (EClinicalMedicine, 2025)
Background - Existing research has shown that prematurity and low birth weight are associated with mental health in children and adolescents, but their impact on mental health in adulthood and the mechanisms involved have been less studied. This study investigated the impact of prematurity and abnormal fetal growth, as a marker for fetal growth restriction, on mental health outcomes in adulthood. - Methods - This retrospective cohort study examined adults aged 18-52 years, categorized by gestational age (extremely preterm: ≤28 weeks; very preterm: 29-32 weeks; moderately preterm: 33-36 weeks; term: ≥37 weeks). The cohort consists of individuals who were either born preterm or at term from 1969 to 2002. Data collection occurred between 2019 and 2021. This exploratory analysis used multivariable logistic regression to assess the impact of prematurity and fetal growth restriction on adult mental health outcomes (measured by the “Patient Health Questionnaire”), adjusting for age, gender, and socioeconomic status. The study also explored the relationship between childhood behavioral problems, retrospectively described by the mothers of the participants (2-4 years), and adult mental health, with separate analyses for preterm and term births. - Findings - The multivariable logistic regression analysis of 606 participants (average age 28·96 ± 8·9 years, 326 females) indicated that a low gestational age of ≤28 weeks was independently associated with an increased prevalence of major depressive disorder (OR = 4·14, CI: 1·43-11·77, p = 0·01) and anxiety disorder (OR = 5·17, CI: 1·51-17·37, p = 0·01) in adulthood compared to a gestational age of ≥37 weeks. A low birth weight percentile was not associated with mental disorders. Further regression analysis revealed that peer problems and emotional problems in childhood were significantly associated with major depression in adulthood in participants born preterm. The sensitivity analysis revealed that the previously observed association between the gestational age group of ≤28 weeks and major depressive disorder was no longer statistically significant (OR = 2·84, CI: 0·85-9·07, p = 0·08) when the model was adjusted for maternal smoking and alcohol consumption during pregnancy. The association between the extreme preterm group and generalized anxiety disorder remained significant (OR = 4·63, CI: 1·27-16·22, p = 0·02). - Interpretation - This study provides exploratory insights into the complex impact of prematurity on mental health in adulthood, highlighting the vulnerability of the extremely preterm group (≤28 weeks) from a multi-informant, lifespan perspective. It emphasizes the importance of continuous monitoring and psychosocial support for those born extremely preterm, from infancy through adulthood, to mitigate potential adverse mental health outcomes. - Funding - The Gutenberg Prematurity Study was supported by the Ernst und Berta-Grimmke Stiftung, Stufe 1 support of the UM and the Else Kröner-Fresenius-Stiftung.